Konstantin Bol’šakov: letters to Anna Chodasevič - Bogomolov, Nikolaj; Maurizio, Massimo (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
Konstantin Bol’šakov: Letters to Anna Chodasevič. The letters written by Konstantin Bolshakov to Anna Khodasevich in 1916 represent a unique testimony of the biography of Bolshakov at that time, a few years before the dramatic experience the poet will live on the Russian front during WWI.